Extracts of Tagetes erecta exhibit potential cytotoxic and antitumor activity that could be employed as a promising therapeutic agent against cancer: A study involving in vitro and in vivo approach - Dharmeswar Barhoi; Puja Upadhaya; Sweety Nath Barbhuiya; Anirudha Giri; Sarbani Giri (Elsevier, 2022)
Background and purpose: Globally, the burden of cancer is increasing consistently. Modern cancer therapies include lots of toxicity in the non-targeted organs reducing the life expectancy of the patients. Therefore, the development of safer alternative medicines with less toxicity and high efficacy is of immense importance. The present study was designed to evaluate the anticancer activity of a medicinal plant, "Tagetes erecta L." (TE), in established cancer cell lines in vitro and in animal models in vivo. Methods: GC-MS analysis was performed to reveal the bioactive compounds present in the leaves of TE. To evaluate the antitumor potential of aqueous extract of TE (AETE), EAC (Ehrlich ascites carcinoma) induced solid tumor model was prepared in Swiss albino mice. The effect of AETE on body weight (BW), tumor weight (TW), and tumor volume (TV) was assessed in control and tumor-bearing animals. Further, the survival of the experimental animals was also monitored to assess the effect of AETE on life span. To determine the cytotoxicity induced by AETE, trypan blue dye exclusion assay, MTT assay, and LDH release assay was performed in EAC and HEp-2 cell lines by in vitro methods. Further, cell cycle assay and apoptosis assay was employed to ascertain the AETE-induced cytotoxicity is due to apoptosis or not. In addition, we have done a mitochondrial membrane potential assay using a flow cytometer to understand the mechanism of apoptosis. Results: GC-MS analysis revealed the presence of hexadecanoic acid, Linolenic acid, Quinic acid, 2,3- dihydro benzofuran (Coumaran), and β-stigmasterol as major bioactive compounds in TE leaves. Results in animal studies showed that AETE treatment potentially reduced the TW and TV and increased the life span in EAC-induced tumor-bearing animals. Side effect analysis was also done in normal Swiss albino mice that confirmed the lack of toxicity of AETE. Studies in cancer cell lines indicated dose and time-dependent cytotoxicity in HEp-2 and EAC cells. Flow cytometric analysis established significant induction of apoptosis in EAC cells without arresting the cell cycle. In addition, AETE treatment led to a significant increase in cells with depolarised mitochondrial membrane potential. Conclusion: The present study indicated that AETE potentially inhibits tumor progression without disturbing normal body physiology. Thus, we conclude that AETE can be used as a potential therapeutic agent against cancer.